The Political Party's Transparency in Financial Assistance Management by Law Number 2 of 2011 on Political Parties - Piyo, Sofyan; Kasim, Nur Mohamad; Wirasaputri, Nina Merantie (Damhil Law Journal, 2021)
This research affords an analysis of political party's transparency in financial assistance management in political parties from the regional budget in Gorontalo District. This research is carried out in five political parties with the most seats in the Regional Representative Council in Gorontalo District, i.e., Golongan Karya party, Demokrat Indonesia Perjuangan party, Amanat Nasional party, Nasional Demokrat party, and Demokrat party. This is empirical research. Results demonstrate that the political parties do not apply transparency in managing financial assistance from the regional budget.